A Link Between Attitudinal and Behavioral Loyalty of Service Customers. Issue 2 (July 2020) - Saini, Shivani; Singh, Jagwinder
Abstract: Past research works in the area of customer loyalty are insufficient to provide clear understanding of linkage in attitudinal and behavioral loyalty. In order to explain this linkage, present research tests the relationship between two forms of customer loyalty: attitudinal and behavioral. The study employs survey methodology to collect the responses from 600 customers of health clinics, fitness centers, beauty salons, and convenience stores. The data were collected through a structured questionnaire with a series of statements based on a 7-point Likert scale. To examine the bilateral relationships, a non-recursive model was implemented using structural equation modeling in Amos 17.0 designed for data analytics. The results reveal that attitudinal loyalty drives behavioral loyalty, while behavioral to attitudinal loyalty has been insupportable across the sample collected from diverse service categories. The study provides insights about the design of marketing strategies in targeting customers' attitudinal loyalty, so that positive behavioral responses can be obtained to sustain the growth and profitability. This research adds value to the growing body of literature on customer loyalty by identifying the relationships between two broad dimensions: attitudinal and behavioral. The study empirically substantiates that an attitude–behavior relationship is significant to achieve true customer loyalty.